The International Soft Tissue Sarcoma Consortium: The baseline analysis of rhabdomyosarcoma data - Bisogno, Gianni; Sparber-Sauer, Monika; Rodeberg, David; Merks, Johannes H M; Koscielniak, Ewa; Wolden, Suzanne L; De Salvo, Gian Luca; Del Bianco, Paola; Xue, Wei; Ebinger, Martin; Vokuhl, Christian; Venkatramani, Rajkumar; et al. (John Wiley & Sons Inc., 2025)
Background: The International Soft Tissue Sarcoma Consortium (INSTRuCT) was established in 2017 to enhance international collaboration. This study describes the characteristics of rhabdomyosarcoma (RMS) patients in the INSTRuCT database and examines differences across contributing groups. Methods: INSTRuCT includes data Children’s Oncology Group (COG), Cooperative Weichteilsarkom Studiengruppe (CWS), and European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) along with prior studies from Malignant Mesenchymal Tumour Committee (MMT) and Italian Soft Tissue Sarcoma Committee (STSC). Data standardization was supported by the University of Chicago’s Pediatric Cancer Data Commons. Pseudonymized patient-level data from clinical trials were harmonized. Differences across groups were assessed using χ2 or Kruskal–Wallis tests. Results: As of March 2025, INSTRuCT includes 6972 RMS patients from 16 trials (1990–2016). Embryonal RMS was the most common histology in all groups (range, 45.4%–62.2%). Alveolar RMS was less frequent in EpSSG (26.8%) although the rate of RMS fusion-positive was comparable across groups (74.6%–81.9%). COG and EpSSG had more T1 tumors, (53.2% and 51.4%) with COG reporting more tumors <5 cm (52%). Nodal involvement was least reported in MMT (15.4%). Metastatic patients were less represented in MMT (11%) and EpSSG (13.3%). Tumor site distribution varied: genitourinary nonbladder/prostate RMS was more common in COG, whereas head and neck nonparameningeal and orbital RMS were more represented in MMT and STSC. MMT had fewer completely resected tumors (8.9%). Conclusion: Differences among RMS study populations reflect evolving diagnostic criteria and treatment strategies that should be considered in future analyses. INSTRuCT offers a valuable international data set for RMS research.
Keywords: Adolescent; Adult; Child; Child, Preschool; Databases, Factual; Female; Humans; Infant; Male; Rhabdomyosarcoma/pathology; Sarcoma/pathology; Soft Tissue Neoplasms/pathology; Young Adult; Journal Article